Quality of life during the first year after partial laryngectomy: Longitudinal study. Issue 6 (8th February 2018) - Clasen, Daniel; Keszte, Judith; Dietz, Andreas; Oeken, Jens; Meister, Eberhard F.; Guntinas‐Lichius, Orlando; Pabst, Friedemann; Büntzel, Jens; Jenzewski, Eva‐Maria; Singer, Susanne; Meyer, Alexandra
Abstract: Background: This prospective study was conducted to assess changes in quality of life (QOL) of patients who undergo a partial laryngectomy. Methods: The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaires Core and Head and Neck (EORTC‐QLQ‐C30, QLQ‐H&N35) were used preprocedure (n = 218), 1 week (n = 159), 3 months (n = 122), and 1 year after partial laryngectomy (n = 88). Changes over time were analyzed with the Wilcoxon signed rank test and the Holm‐Bonferroni method, and interpreted regarding clinical relevance. Results: Most subscales worsened 1 week postprocedure, but many recovered to baseline level after 1 year. Dyspnea and cognitive functioning deteriorated over time, with worst scores recorded after 1 year. Financial difficulties and fatigue increased after surgery and maintained that level throughout the follow‐up period; sticky saliva remained worse than at baseline, despite some improvements over time. Conclusion: The discovered limitations of QOL should be observed more closely during follow‐up treatment, and patients should be informed about these potential effects before partial laryngectomy.